Endovascular Approach to Acute Hemorrhage in Locally Advanced Breast Cancer. Issue 2 (21st January 2015) - Ugras, Stacy; Gemignani, Mary L.; Connolly, Peter H.; Finley, David J.
Abstract We report a case of a woman with recurrent axillary fungating breast cancer who developed catastrophic hemorrhage from tumor erosion of her axillary artery. This was treated successfully with endovascular placement of a covered arterial stent. We discuss the suitability of endovascular therapy for patients with advanced malignancy given its lower morbidity in this population with decreased life expectancy.